2020
DOI: 10.1007/s00405-020-05813-2
|View full text |Cite
|
Sign up to set email alerts
|

Snoring: is a reliable assessment possible?

Abstract: Purpose It is not easy to assess how severe and annoying a patient's snoring is. Solid parameters are lacking; snorers cannot deliver a reliable self-assessment and it is uncertain whether bed partners' statements can be relied upon. The purpose of the present study was therefore to investigate whether and how well snoring assessment based on acoustic parameters and bed partners' reporting agree. Methods In a double-blind, placebo-controlled study on snoring treatment, several acoustic parameters [snoring inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, in line with a previous study [ 21 ], the present study suggested that the perceived annoyance of snorers’ bedpartners may be used as a reliable assessment of the severity/annoying degree of snoring. However, some other studies suggested the potential influence of listeners’ subjectivities on perceived annoyance of snoring sound and concluded that subjectively evaluated snoring severity should be interpreted with caution [ 13 , 14 ]. Regarding the conflicting results on listeners’ subjectivities and perceived annoyance of snoring sound, this may be due to different study designs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in line with a previous study [ 21 ], the present study suggested that the perceived annoyance of snorers’ bedpartners may be used as a reliable assessment of the severity/annoying degree of snoring. However, some other studies suggested the potential influence of listeners’ subjectivities on perceived annoyance of snoring sound and concluded that subjectively evaluated snoring severity should be interpreted with caution [ 13 , 14 ]. Regarding the conflicting results on listeners’ subjectivities and perceived annoyance of snoring sound, this may be due to different study designs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the subjective annoyance level, as perceived by bedpartners, researchers also explored the possibility to subjectively evaluate snoring [ 10 , 11 ]. Previous studies investigated the association between the acoustic characteristics of snoring sound and subjective annoyance level, and reported conflicting results [ 12 , 13 , 14 , 15 , 16 ]. Fischer et al [ 12 ] found that a score calculated based on the loudness and roughness of snoring sound showed a highly significant correlation with perceived annoyance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Previous snoring monitors considered several acoustical indexes, such as sound pressure level, sound energy, and percentage snoring time. 3 Since one of the main constituents of exhaled gas is water molecules, the humidity of exhaled gas varies with the intensity and rate of breathing. Hence, applying humidity sensors with ultratime stability to sensing snoring is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made in literature to classify and characterize breathing sounds such as snoring through acoustical [5] and psycho-acoustical features such as annoyance [6,7]. If snoring while sleeping at home is the condition, acoustical and psychoacoustic measures of snoring events in the natural home environment will be most appropriate if ambient acoustical influences can be controlled [8].…”
Section: Introductionmentioning
confidence: 99%